Future research priorities for morbidity control of lymphedema - S R Narahari; Madhur Guruprasad Aggithaya; Christine Moffatt; T J Ryan; Vaughan Keeley; B Vijaya; P Rajendran; S B Karalam; S Rajagopala; N K Kumar; K S Bose; K V Sushma (Wolters Kluwer Medknow Publications, 2017)
Background: Innovation in the treatment of lower extremity lymphedema has received low priority from the governments and pharmaceutical industry. Advancing lymphedema is irreversible and initiates fibrosis in the dermis, reactive changes in the epidermis and subcutis. Most medical treatments offered for lymphedema are either too demanding with a less than satisfactory response or patients have low concordance due to complex schedules. A priority setting partnership (PSP) was established to decide on the future priorities in lymphedema research. Methods: A table of abstracts following a literature search was published in workshop website. Stake holders were requested to upload their priorities. Their questions were listed, randomized, and sent to lymphologists for ranking. High ranked ten research priorities, obtained through median score, were presented in final prioritization work shop attended by invited stake holders. A free medical camp was organized during workshop to understand patients' priorities. Results: One hundred research priorities were selected from priorities uploaded to website. Ten priorities were short listed through a peer review process involving 12 lymphologists, for final discussion. They were related to simplification of integrative treatment for lymphedema, cellular changes in lymphedema and mechanisms of its reversal, eliminating bacterial entry lesions to reduce cellulitis episodes, exploring evidence for therapies in traditional medicine, improving patient concordance to compression therapy, epidemiology of lymphatic filariasis (LF), and economic benefit of integrative treatments of lymphedema. Conclusion: A robust research priority setting process, organized as described in James Lind Alliance guidebook, identified seven priority areas to achieve effective morbidity control of lymphedema including LF. All stake holders including Department of Health Research, Government of India, participated in the PSP.